ATTITUDE TOWARDS MENTAL ILLNESS IN SOUTHEASTERN NIGERIA: THE CONTRADICTIONS OF A COMMUNITARIAN CULTURE. Issue 2 (March 2016) - Ikwuka, Ugo; Galbraith, Niall; Manktelow, Ken; Chen‐Wilson, Josephine; Oyebode, Femi; Muomah, Rosemary C.
Abstract : The effect of mental illness stigma can be greater in the developing world where sufferers are additionally affected by destitution. This study investigated the attitudes of the Igbo people of Southeastern Nigeria toward mental illness to establish the extent and determinants of negative attitudes. Multistage sampling was used to select participants (n = 602), to whom questionnaires were administered. More than half of all the demographic groups demonstrated authoritarian attitude and primary social distance. A third of the sample equally endorsed social restrictiveness, anticommunity care, and secondary social distance. Low education, male gender, older age, Protestant denomination, and not being familiar with people with mental illness predicted more negative attitudes. Culture, stereotypes, causal explanations, and poor mental health knowledge were the leading mediators of negative attitudes. The determinant role of culture and demographic variables in the stigma dynamics indicate that contextualized and targeted interventions could be more effective than general campaigns.